Do Trajectories of Sensation Seeking Vary by Sex and Child Maltreatment Subtypes?. Issue 5 (March 2022) - Sussman, Tamara J.; Santaella-Tenorio, Julian; Duarte, Cristiane S.; Wall, Melanie M.; Ramos-Olazagasti, Maria; Suglia, Shakira F.; Canino, Glorisa; Bird, Hector; Martins, Silvia S.
Child maltreatment and elevated sensation seeking are associated with a wide range of negative outcomes. Longitudinal data from a study of Puerto Ricans living in two sociocultural contexts were used to determine whether child maltreatment subtypes, sex, or sociocultural context relate to trajectories of sensation seeking. Participants were 2, 489 individuals from the Boricua Youth Study (48.5% girls) living in New York and in Puerto Rico (PR; 5–15 years old at Wave 1). Subtypes of child maltreatment were measured using child report on the Parent–Child Conflict Tactics Scale and the Sexual Victimization Scale at Wave 1. The association between child maltreatment subtypes, sex, sociocultural context, and previously established sensation-seeking trajectories across three waves of data collection was probed using multinomial logistic regression. Girls, but not boys, who experienced neglect (adjusted odds ratio; AOR; 95% confidence interval [95% CI] = 5.33 [1.35, 21.03]), or physical abuse (AOR [95% CI] = 3.66 [1.07, 12.54]), were more likely to have an elevated sensation-seeking trajectory than a normative trajectory. For boys, none of the maltreatment subtypes were linked to the elevated sensation-seeking class. Girls exposed to verbal abuse (AOR [95% CI] = 0.33 [0.15, 0.75]) and boys exposed to physical abuse (AOR [95% CI] = 0.39 [0.16, 0.97]) were less likely to belong to the low sensation-seeking class. No significant interactions between sociocultural context (i.e., PR vs. New York) and maltreatment subtype on the development of sensation seeking were found. This research suggests sensation-seeking levels vary by experiences of childhood maltreatment, and that sex moderates the relationship between child maltreatment experiences and sensation seeking, with an association between some maltreatment subtypes and elevated sensation-seeking trajectories found in girls, but not boys. These results underline the importance of considering sex when examining how child maltreatment relates to outcomes.